2016
DOI: 10.1371/journal.pone.0161963
|View full text |Cite
|
Sign up to set email alerts
|

Genetics, Gene Flow, and Glaciation: The Case of the South American Limpet Nacella mytilina

Abstract: Glacial episodes of the Quaternary, and particularly the Last Glacial Maximum (LGM) drastically altered the distribution of the Southern-Hemisphere biota, principally at higher latitudes. The irregular coastline of Patagonia expanding for more than 84.000 km constitutes a remarkable area to evaluate the effect of Quaternary landscape and seascape shifts over the demography of near-shore marine benthic organisms. Few studies describing the biogeographic responses of marine species to the LGM have been conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 135 publications
(195 reference statements)
0
14
0
Order By: Relevance
“…Strong demographic and geographic expansion following post-glacial sea level rise may also be a suitable explanation for the low levels of genetic diversity and the high degree of genetic homogeneity in S. lessonii across these provinces. This pattern of genetic structure has been found in several Magellan marine benthic near-shore organisms with dispersive potential including invertebrates 20,55 , vertebrates 14,22 and macroalgae 19,27 . Finally, in contrast to recent phylogeographic analyses in sub-Antarctic invertebrates including Siphonaria species 21 , isopods 57 , and patellogastropods 20,55 , we found in S. lessonii a complete absence of genetic structure between continental Magellan and the Malvinas/Falkland Islands populations.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Strong demographic and geographic expansion following post-glacial sea level rise may also be a suitable explanation for the low levels of genetic diversity and the high degree of genetic homogeneity in S. lessonii across these provinces. This pattern of genetic structure has been found in several Magellan marine benthic near-shore organisms with dispersive potential including invertebrates 20,55 , vertebrates 14,22 and macroalgae 19,27 . Finally, in contrast to recent phylogeographic analyses in sub-Antarctic invertebrates including Siphonaria species 21 , isopods 57 , and patellogastropods 20,55 , we found in S. lessonii a complete absence of genetic structure between continental Magellan and the Malvinas/Falkland Islands populations.…”
Section: Discussionmentioning
confidence: 59%
“…This pattern of genetic structure has been found in several Magellan marine benthic near-shore organisms with dispersive potential including invertebrates 20,55 , vertebrates 14,22 and macroalgae 19,27 . Finally, in contrast to recent phylogeographic analyses in sub-Antarctic invertebrates including Siphonaria species 21 , isopods 57 , and patellogastropods 20,55 , we found in S. lessonii a complete absence of genetic structure between continental Magellan and the Malvinas/Falkland Islands populations. The presence of a free-living dispersive stage in S. lessonii, absent in other sub-Antarctic Siphonaria species, seems to play a key role establishing genetic homogeneity across thousands of kilometers from Chiloé Island to Uruguay in the southwest Atlantic.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Quaternary glacial processes in the Southern Ocean severely affected the demography of shallow benthic populations as has been demonstrated in several population‐based studies (e.g. Allcock & Strugnell, ; Fraser et al., ; González‐Wevar, Saucède, Morley, Chown, & Poulin, ; González‐Wevar et al., , ; Nikula et al., ; Thornhill et al., ). Repeated ice advances and retreats would have generated massive reductions in population sizes (or even local extinctions) and consequent severe declines in genetic diversity.…”
Section: Discussionmentioning
confidence: 90%
“…Unexpectedly, our results showed that haplotypes of S. lateralis from FI are clearly differentiated (≥8 steps away) from those of other localities, including adjacent areas such as Patagonia. Evidence of genetic differentiation between PP and FI populations has been recorded in crustaceans like Parawaldeckia kidderi (Nikula et al., ), and Serolis paradoxa (Leese et al., ) and limpets of the genus Nacella (González‐Wevar et al., , ). Due to their geographical position, the FI were less affected by Quaternary glaciations than other areas of the Southern Ocean (Hodgson et al., ).…”
Section: Discussionmentioning
confidence: 99%